Applying meta-functions for improving JavaScript code performance - Medel, Ricardo (2017)
In recent years, the expansion of the World Wide Web, and web runtimes in particular, to all kind of devices has rendered the JavaScript performance in a hot topic. Several approaches to improve the performance of JavaScript applications have been tried by the industrial and research communities. In this paper we review the most popular approaches and propose a novel solution based on meta-programming and source code rewriting. The preliminary results of our experiments are very promising, although more studies are required to know to what extent this approach can improve the performance of real-life JavaScript programs.